Characteristics and trends in incidence of childhood cancer in Beijing, China, 2000-2009 - Yang, Lei; Yuan, Yannan; Sun, Tingting; Li, Huichao; Wang, Ning (Chinese Journal of Cancer Research; Vol 26, No 3 (June 01, 2014): Chinese Journal of Cancer Research, 2014)
Objective: To investigate the characteristics and incidence trends of childhood cancer in Beijing, China, from 2000 to 2009. Methods: A total of 1,274 cases with childhood cancer in Beijing from 2000 to 2009 were included in the study. All rates were age-standardized using the direct method to the world standard population and expressed per million person-years. Incidence trends were characterized by calculating annual percent change (APC) using Joinpoint Regression Program. Results: The crude incidence rate was 106.47 per million [age-standardized rate (ASR) 113.34] between 2000 and 2009 in Beijing with the most common diagnoses, leukemia (N=505, 39.64%, ASR 45.20), followed by central nervous system (CNS) tumors (N=228, 17.90%, ASR 19.28) and lymphoma (N=91, 7.14%, ASR 6.97). The incidence for all childhood cancers combined has increased during the study period, with an APC of 5.84% [95% confidence interval (95% CI): 1.0-10.9] after adjusted by world population. The ASR of all combined cancers in boys showed a slight, but no significant increase, with an APC of 5.33% (95% CI: –0.6- 11.6); for girls, the trends increased significantly, with an APC of 6.54% (95% CI: 1.5-11.8). Conclusions: The incidence rate of childhood cancer in Beijing was higher than the average level of China and lower than that of western countries. The incidence trends of childhood cancer, especially leukemia among girls showed a significantly increase from 2000 to 2009. While among boys, no substantially change was seen during the observed time period. Some sex-specific trends by subcategories and trends of major cancers in different age groups by cancer site merit further investigation.